(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The present study determined that the essential factor of technogenic influence on the roadside landscapes is a motor complex that leads to the alienation of large territories, destabilizing of the natural ecosystems, the disarticulation of landscapes and an irreversible transformation of nature and territorial complexes in general. The significant influence of motor transport is the exhaust emissions with Carbon (ІІ) oxide, Nitrogen oxides, hydrocarbons, aldehydes, soot (technical carbon), mineral dust, heavy metals, etc., that influence not only on the environment, but also on the health of the population. The migration and deposition of the pollutants that are produced by vehicle flows are caused by many factors of different genesis. In particular, this landscape topographic characteristics and the geochemical territory activity of natural and technogenic geo-ecosystems, structure of biocoenoses, presence of geochemical barriers (including artificially created), density, construction, transport, physical and geographical, social and economic features of transport network infrastructure, the intensity of transport flows, etc. Therefore, to ensure the environmentally safe operation of "car – road – environment" system should include a systematic approach to the development concept of the transport complex within the specific natural and man-made geo-ecosystems with developed automobile and communication networks that would provide not only its economic and transport feasibility, but also minimizing the anthropogenic transformation of natural and territorial complexes in general. To reduce eco-destructive impact we recommend to apply the developed design of forest of gas and dustproof lane road that substantially reduce the dangerous zone of influence.